Artykuł 59a k.k. — sukces czy porażka ustawodawcy - Myrna, Bogdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article focuses on the now repealed measure of discontinuance of criminal proceedings under Article 59a of the Criminal Code following a request of the injured arty in case of damage redress or compensation for the injury caused by the crime. In the article the author criticises the measure in question on many levels, also analysing the grounds for and the mode of discontinuance.
Keywords: prawo karne; sprawność postępowania karnego; kodeks karny - art. 59a